At the Margins of the World: The Nature of Limits in Terrence Malick’s The Thin Red Line - Lord, Catherine M. (Text Matters: A Journal of Literature, Theory and Culture, 2012)
Terrence Malick’s The Thin Red Line (1998) is an anti-war film which can be read as an Orphic narrative meditating on the relationship between humans and “nature.” Many scholarly readings of the film have been attracted by analyzes that explore the influences of Cavell and Heidegger on Malick (Critchley, Furstenau and MacCavoy, Sinnerbrink). Kaja Silverman’s recent opus, Flesh of My Flesh (2009), contains a chapter titled “All Things Shining.” She elegantly examines how Malick’s film explores the theme of “finitude.” She argues that, ontologically speaking, human existence gains a more intense “glow” when humans are made aware of their mortality. The present becomes paramount. But like Orpheus, the present seeks to make amends with the past. Taking Silverman’s analysis one step further involves exploring finitude through the film’s many animal, arboreal and geological images. Nature can be read as a “margin” that more fully enhances the film’s exploration of connection and finitude. To this end, the opening chapter of Jacques Derrida’s Margins of Philosophy (1986) is invaluable. Entitled “Tympan,” Derrida’s introductory essay introduces a wealth of ecological metaphors. These stimulate an interaction between Silverman’s model of finitude, Derrida’s surprising ecologies at the margin and Malick’s quest for what shines in all beings.